2020
DOI: 10.1515/nanoph-2020-0373
|View full text |Cite
|
Sign up to set email alerts
|

Metasurfaces for biomedical applications: imaging and sensing from a nanophotonics perspective

Abstract: Metasurface is a recently developed nanophotonics concept to manipulate the properties of light by replacing conventional bulky optical components with ultrathin (more than 104 times thinner) flat optical components. Since the first demonstration of metasurfaces in 2011, they have attracted tremendous interest in the consumer optics and electronics industries. Recently, metasurface-empowered novel bioimaging and biosensing tools have emerged and been reported. Given the recent advances in metasurfaces in biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(111 citation statements)
references
References 201 publications
(246 reference statements)
0
111
0
Order By: Relevance
“…It was also observed that an increase in the size of the unit-cells of a metasurface could lead to better sensing, especially if nanorods are used, due to their larger surface area. Chiral metasurfaces can also help in sensing DNA and cancer biomarkers, which make chiral metasurfaces a very exciting tool in the field of CD spectroscopy [ 115 ].…”
Section: Applications Of Chiral Metasurfacesmentioning
confidence: 99%
“…It was also observed that an increase in the size of the unit-cells of a metasurface could lead to better sensing, especially if nanorods are used, due to their larger surface area. Chiral metasurfaces can also help in sensing DNA and cancer biomarkers, which make chiral metasurfaces a very exciting tool in the field of CD spectroscopy [ 115 ].…”
Section: Applications Of Chiral Metasurfacesmentioning
confidence: 99%
“…Conventional optical spectroscopic methods for virus identification rely on the use of fluorescent materials such as dyes to label the target biomolecules [ 5 , 3 , 6 , 7 , 8 ]. Lately, immunoassay based on localized surface plasmon resonances (LSPR) has been introduced to improve detection limit at nanoscale for both solution and substrate based metallic nanoparticles [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their interaction with the biomolecules induce detectable spectral changes with considerably reduced sensing footprint [ [29] , [30] , [31] , [32] , [33] , [34] ]. Plasmonic metasurfaces are proposed for detection of low concentration of analyte [ 32 , [35] , [36] , [37] , [38] , [39] , 8 ]. Graphene have been extensively investigated for photovoltaics and energy storage applications [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel metasurface-based lenses are ubiquitous for biomedical applications, 12 such as endoscopy and wearable medical devices. 13 These are replacing conventional bulky optical lenses such as Fresnel micro-lenses and micro-grating, which have limited imaging quality, high cost, inadequate phase coverage, and integration difficulties. The noteworthy advancements in the development of metalenses are the wide eld-of-view, 14,15 high aspect ratio dielectric, 16 achromatic, [17][18][19][20] and tunable metalens.…”
Section: Introductionmentioning
confidence: 99%